HUBUNGAN TINGKAT PENGETAHUAN AKSEPTOR KB DENGAN MINAT PEMAKAIAN KONTRASEPSI AKDR DI PUSKESMAS ULAK KARANG PADANG TAHUN 2017 - Diyana, Mela (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
According to data from the health department of padang in 2016 the number of active family planning acceptors as 112 781 (65.5%) with the number of family planning acceptors IUD (8.11%). Based on data from health centers Padang Ulak 2016 IUD users is still low (1.99%). The purpose of this study was to determine Relations Knowledge Level Of Acceptor family planing With Interests Contraception user IUD In Puskesmas Ulak Karang Padang 2017.This research is an analytic with. cross sectional design The study population was all women who are active acceptors in Puskesmas Padang Ulak Karang during the period from January to May 2017 doo ut as 611 people. A sample of 61 people, the measuring instrument using a questionnaire. Data were analyzed using univariate and bivariate using a computerized programBased on the results found almost half of respondents (49.2%) had low knowledge about contraceptive IUD, more than half of respondents (62.3%) did not interest IUD contraception and there is a relationship of level knowledge of family planning acceptors with the IUD contraceptive user interest in Puskesmas Padang Ulak Karang, 2017. inThe conclusion of their paper snowed that there is relation in the level of knowledge family planing acceptions with used interest of IUD Contraceptive. This reasearch is recomended to be conducted on educational instituions to give this information as subjects to midwifery students.Bibliography: 19 (2005-2017)Keywords: Awareness, Interest, Contraception IUD